Social Workers and the Sociological Sense of Social Problems: Balancing Objectivism, Subjectivism, and Social Construction - Appel Nissen, Maria (Qualitative Sociology Review, 2015)
The aim of this article is to explore the intricate relations between objectivism, subjectivism, and constructionism. I explore the construction of social problems in everyday professional practice as a valuable source for addressing and reflecting on differences in perceptions of knowledge. Using data from a study of how Danish social workers perceive social problems, the article shows how social workers’ perceptions of social problems reveal a sociological sense of social problems that renders possible both ontological assumptions, as well as epistemological reflections on the objective, subjective, and social constructionist dimensions of social problems. The social workers are constructing a model of social problems and how they are reproduced, as well as epistemological reflections on the uncertainty of knowing the “reality” of social problems. Those constructions are not formulated strictly in line with scholarly approaches but rather stem from experiences of working with social problems. The article proposes that we can learn something from this in terms of reimagining social constructionism. I propose that social constructionists should cultivate a sociological sense of the practical perceptions and approaches to solve social problems in society.